Traditional Music Learning for Students Mentally Impaired (Children with Special Needs) in SLB Negeri 2 Padang - Atos, Febrian; Hadi, Harisnal (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study aims to describe and reveal how the process of learning traditional music for students with intellectual disabilities (children with special needs) in SLB Negeri 2 Padang. This type of research is qualitative research using descriptive methods. The researcher's own research instruments and assisted by supporting instruments such as stationery and digital cameras / mobile phone cameras. Collection techniques through observation or observation, interviews, documentation and literature study. The steps in analyzing data are data classification, data clarification, analyzing data, describing data and inferring data. Based on the results of the study, it was revealed that the learning planning carried out by SLB Negeri 2 Padang began with assessment, which means paying attention and sorting out the material to be taught according to student conditions and prioritizing adaptive and flexible learning according to student abilities. The method of lectures and demonstrations carried out directly by the teacher makes students better understand the material in general then continued with practice and exercises that are guided repeatedly by the teacher with patience and supported by continuous motivation and appreciation. So that with the condition of students who have special needs for the mentally impaired and music art teachers who do not come from special education, students with intellectual disabilities class IX C SLB Negeri 2 Padang are able to learn traditional music and are able to play traditional music in accordance with the expected goals.